Expression of several common melanocyte-associated antigens in human epidermal melanocytes in vitro. - Chen, R.H.; Zhang, R-Z.; Wang, S.W.; Li, Y. (European Journal of Pediatric Dermatology, 2020)
The study of melanocytes in vitro is important for the treatment of pigment-related dis-eases. By means of immunofluorescence, we used anti-HMB45, T311, MITF, Nestin, Ki67 and CD146 antibodies to investigate the expression of corresponding antigens in human epidermal melanocytes in vitro. The results showed that all melanocytes were positive for HMB45, T311, MITF, Nestin and CD146 and some melanocytes were Ki67 negative. These results help us to select suitable antibodies to identify melanocytes cultured in vitro and recognize the different states of differentiation and proliferation of these cells.